Depression, anxiety and stress among undergraduate students during COVID‐19 outbreak and "home‐quarantine" - Shaher H. Hamaideh; Hanan Al‐Modallal; Mu'ath Tanash; Ayman Hamdan‐Mansour3 (Wiley, 2022)
Abstract Aim Many people including students affected physically and psychologically by coronavirus disease (COVID‐19) outbreak and "home‐quarantine." This study aimed at assessing the prevalence and predictors of depression, anxiety and stress among university students in Jordan during "home‐quarantine" due to the outbreak of COVID‐19. Design This is a cross‐sectional descriptive study. Methods Data were collected from a convenience sample of 1,380 Jordanian university students. A web‐based survey was used to collect data from the participants using the DASS‐21. Results The prevalence of depression, anxiety and stress in different levels was 78.7%, 67.9% and 58.7%, respectively, which are higher during "home‐quarantine." The mean scores of depression, anxiety and stress were at moderate levels. Strong correlations were found between depression, stress and anxiety, with demographic, health‐related, lifestyle variables. Several variables also predicted depression, stress and anxiety.